2020
DOI: 10.1016/j.chb.2020.106469
|View full text |Cite
|
Sign up to set email alerts
|

Stress in manual and autonomous modes of collaboration with a cobot

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 60 publications
4
29
0
Order By: Relevance
“…We can also speak about the ethics of technique: human intelligence connected with artificial intelligence by cobots and how it relates to cyber-physical systems. Indeed, the integration of robotic systems is not neutral for human health and well-being, for example (Pollak et al, 2020). In today's factories, we can identify several ethical trends influencing standardized workplace organization:…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…We can also speak about the ethics of technique: human intelligence connected with artificial intelligence by cobots and how it relates to cyber-physical systems. Indeed, the integration of robotic systems is not neutral for human health and well-being, for example (Pollak et al, 2020). In today's factories, we can identify several ethical trends influencing standardized workplace organization:…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, automating ADLs, as suggested in research, can have unintended consequences. Pollak et al conducted a study comparing manual and autonomous modes of collaboration with a collaborative robot (cobot) [21]. They found that using the manual mode in which the cobot would perform tasks only upon interaction with the participants decreased stress significantly.…”
Section: Related Workmentioning
confidence: 99%
“…We refer to the definition of stress provided by Folkman and Lazarus as "a particular relationship between the person and the environment that is appraised by the person as taxing or exceeding his or her resources and endangering his or her well-being" [144]. In pHRI, stress is determined by "the changes in the nature of the work (from physical to mental activities), the proximity of the robot to the human operator and the robot's movement, or the loss of control that can stem from the automation of robotic agents", as defined by Pollak et al in [43]. A related concept is that of robostress, defined by Vanni et al as "a human estimated or perceived stress when working with the interactive physical robots" [145].…”
Section: Stress (Or Strain)mentioning
confidence: 99%